PERAN KEBIJAKAN MONETER DALAM MENJAGA STABILITAS EKONOMI DAN PERTUMBUHAN BERKELANJUTAN DI INDONESIA - Oktaviani, Devi; Almas Sabila Putri; Louis Anugrah Nusantara Goeltom; Siti Nurfaidah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The monetary sector and policy play a vital role in maintaining a nation’s economic stability and fostering sustainable growth. Monetary policy, as implemented by central banks, aims to regulate money supply, interest rates, and inflation to ensure macroeconomic equilibrium. In recent years, the effectiveness of monetary instruments has been tested by global financial volatility, exchange rate fluctuations, and domestic fiscal pressures. This study explores the interaction between the monetary sector and policy decisions, analyzing how strategic adjustments in monetary tools such as open market operations, reserve requirements, and benchmark interest rates affect inflation control, investment growth, and public consumption patterns. The discussion also highlights the role of monetary transmission mechanisms and coordination with fiscal policy to optimize policy outcomes. The findings suggest that consistent, transparent, and adaptive monetary policies are essential in stabilizing financial systems and supporting long-term economic resilience.